2015
DOI: 10.1002/app.42356
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically strong nanocomposite films based on highly filled carboxymethyl cellulose with graphene oxide

Abstract: Biopolymer nanocomposite films were prepared by adding exfoliated graphene oxide nanosheets (GOn) into carboxymethyl cellulose (CMC) at low and high GOn loadings (0.4–7 wt %). As firstly evidenced by viscosity of film-forming solutions, microscopic observations and infrared spectroscopy measurements, it was found that the GOn form a three-dimensional network throughout strong interfacial interactions with CMC, confirming that the GOn were well dispersed within the CMC, even at high GOn content, owing to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 60 publications
(118 reference statements)
1
19
0
Order By: Relevance
“…12 It was generally observed that GO started to aggregate in the polymer composites at the higher loading levels, due to the sheet-to-sheet interaction caused by the inadequate compatibility between the sheet and the polymer chains. 31,32 The mechanical properties in this work were continuously improved up to 3 wt% of GO loading in both types of composites, indicating well dispersed and distributed NGO sheets within both the CNF and TCNF matrices as already evidenced by SEM observations.…”
Section: Mechanical Propertiessupporting
confidence: 73%
“…12 It was generally observed that GO started to aggregate in the polymer composites at the higher loading levels, due to the sheet-to-sheet interaction caused by the inadequate compatibility between the sheet and the polymer chains. 31,32 The mechanical properties in this work were continuously improved up to 3 wt% of GO loading in both types of composites, indicating well dispersed and distributed NGO sheets within both the CNF and TCNF matrices as already evidenced by SEM observations.…”
Section: Mechanical Propertiessupporting
confidence: 73%
“…The water absorbency of ST/L-GO bionanocomposites was lower than that of the ST/L blend, suggesting that the addition of GO nanosheets prevents the prepared films from the absorption of water when exposed to the moisture. 65 The incorporation of GO in the cross-linked ST/L matrix resulted in a slight improvement of thermal stability at a loading amount of 0.3−0.5 wt % of GO because the residue increases with increasing amounts of GO.…”
Section: Resultsmentioning
confidence: 99%
“…The stretching vibration of O−H blue shifts to 3433 cm −1 , which indicates the formation of the composite is facilitated by H-bonding interaction between CGO and CMC. On the other hand, the carbonyl stretch of carboxylate groups of CMC was overlapped with that of carboxylic groups of CGO at about 1577 cm −1 , which is attributable to the interaction between the hydroxyl groups of CMC and the carboxyl groups of CGO [ 44 , 53 ]. In addition, it is worthwhile mentioning that the new peak at 1654 cm −1 is assigned to −NH(R) functional groups [ 54 ], suggesting that EDA produced a covalent bond during cross-linking with CGO, in consistent with the Raman analysis.…”
Section: Resultsmentioning
confidence: 99%